A mixed ion conductor material and its preparation method and application
By adopting a mixed ion conductor material with core-shell structure, using the core of solid electrolyte material and carbonization precursor material and the shell of the carbon layer, the problem of lack of lithium ions and sodium ions can be transmitted simultaneously in the prior art, and high conduction is achieved Lithium ion performance and low interface resistance have promoted the development of solid-state hybrid lithium-sodium batteries.
Patent Information
- Application Number
- CN202111518200.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-12-13
AI Technical Summary
The prior art lacks mixed ion conductor solid electrolyte materials that can conduct lithium ions and sodium ions simultaneously, limiting the development of solid mixed lithium sodium batteries.
The hybrid ion conductor material adopts a core-shell structure. The core consists of solid electrolyte material NaxAyZr2-ySix-y-1P4-x+yO12 and carbonization precursor material. The shell is a carbon layer. The conductive properties and phase of the material are improved through carbon coating technology. Capacity.
The high conduction lithium ion performance and low interface resistance of the material are achieved, the compatibility with the positive and negative electrodes is enhanced, the unstable reaction is reduced, and the development of solid-state hybrid lithium sodium batteries is promoted.
Smart Images

Figure CN114267871B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a mixed ion conductor material and a preparation method and application thereof. Background Art
[0002] The rapid development of new energy vehicles, large-scale energy storage power stations and micro devices has put forward higher requirements for the energy density, power density, working environment and safety of secondary batteries. Therefore, solid-state lithium batteries, as the most promising electrochemical energy storage devices, have received extensive attention and research in recent years. With the large-scale manufacture and application of lithium-ion batteries, the relatively scarce lithium resources in nature have become even more scarce. The abundance of sodium in the earth's crust is much higher than that of lithium. Sodium and lithium are in the same main group, and their chemical and physical properties are similar. Therefore, the development of solid-state sodium-ion batteries can greatly reduce the cost of batteries. Because sodium has the advantages of abundant raw materials and low cost, it has become a research hotspot in the field of new energy devices and new materials. As a new generation of batteries, solid-state sodium batteries are considered to be the future substitutes for solid-state lithium batteries. Their working principle is similar to that of lithium batteries, and they have certain commonalities in performance research and material research and development. However, since the ionic radius of Na+ is larger than that of Li+, the reversible insertion and extraction process of sodium ions in the electrode material is limited, thereby affecting the electrochemical performance of the battery (Kim, H., Ding, Z., Lee, MH, et al. Adv. Energy Mater. 2016, 6, 1600943.).
[0003] In 2006, J.Baker et al. first proposed the concept of hybrid lithium-ion batteries. Using liquid electrolytes, hybrid lithium-sodium-ion batteries show better electrochemical performance than sodium-ion batteries and are cheaper than pure lithium-ion batteries. However, solid-state hybrid lithium-sodium-ion batteries are rarely reported because of the lack of mixed ion conductor solid electrolyte materials that can conduct lithium ions and sodium ions at the same time. The development of solid-state hybrid ion conductor materials can help promote the development of hybrid solid-state lithium-sodium batteries. Summary of the invention
[0004] The embodiment of the present invention provides a mixed ion conductor material and a preparation method and application thereof. The mixed ion conductor material of the present invention is a core-shell structure, and the material has good compatibility with positive and negative electrodes, low interface resistance, and has the advantages of being able to conduct lithium ions and sodium ions.
[0005] In a first aspect, an embodiment of the present invention provides a mixed ion conductor material, including a two-layer structure of a core and a shell;
[0006] The inner core comprises a first component and a second component;
[0007] The first component is a solid electrolyte material with a chemical formula of Na x A y Zr 2-y Si x-y-1 P 4-x+y O 12 , wherein A includes one or more of Al, Cr, Fe, Ga, Se, Y, In or La, and 2.5≤x≤3.5, 0<y≤1;
[0008] The second component is amorphous carbon and / or crystalline carbon formed by carbonization of a carbonization precursor material;
[0009] The shell is a carbon layer.
[0010] Preferably, the carbonization precursor material includes: one or more combinations of glucose, sucrose, citric acid, epoxy resin, phenolic resin, and urea-formaldehyde resin.
[0011] Preferably, the structure of the carbon layer includes one or more of a continuous film, a discontinuous film or closely arranged carbon particles; the thickness of the carbon layer is between 1 nm and 2 μm, and the coverage of the carbon layer on the surface of the core is 50% to 100%;
[0012] The second component is uniformly embedded and distributed in the first component, and the particle size of the formed core is between 30nm-100μm; the mass ratio of the first component, the second component and the carbon layer is 1:(0-0.6):(0.002-0.6);
[0013] The particle size of the mixed ion conductor material is between 31 nm and 102 μm.
[0014] Preferably, the shape of the mixed ion conductor material is one or more of spherical, ellipsoidal, pebble-shaped, flake-shaped or irregular.
[0015] In a second aspect, an embodiment of the present invention provides a method for preparing the mixed ion conductor material according to the first aspect, the preparation method comprising:
[0016] Uniformly mixing the first component and the second component according to the required mass fraction to obtain a precursor powder;
[0017] The precursor powder is placed in a reaction device, and the temperature is raised from room temperature to 700°C-1200°C under an inert atmosphere, and kept for 1 hour to 20 hours;
[0018] crushing the carbonized material to obtain a core material;
[0019] The core material is carbon coated to obtain a mixed ion conductor material with a core-shell structure.
[0020] Preferably, the inert gas includes one or more of nitrogen, helium, neon and argon.
[0021] Preferably, the carbon coating method is specifically a liquid phase method or a solid phase method;
[0022] The liquid phase method comprises: dissolving and mixing the core material and the soluble carbon source material in a solvent, and then drying the dried sample, and carbonizing the dried sample at 700° C.-1200° C. for 1 hour-20 hours;
[0023] The solid phase method comprises: mixing the core material and the solid phase carbon source material uniformly, and then carbonizing them at 700° C. to 1200° C. in an inert atmosphere for 1 hour to 20 hours.
[0024] Further preferably, the soluble carbon source material comprises: one or more of glucose, sucrose, citric acid, and epoxy resin;
[0025] The solid carbon source material includes: one or more of graphite, activated carbon, carbohydrate, acetylene black, mesoporous carbon, graphene, phenolic resin, furfural resin, urea-formaldehyde resin, asphalt, polyvinyl chloride, polyethylene glycol, and polyvinyl butyral.
[0026] In a third aspect, an embodiment of the present invention provides an application of the mixed ion conductor material described in the first aspect above, wherein the mixed ion conductor material can be used as a battery positive electrode material additive, a diaphragm coating material additive, a diaphragm coating material or a negative electrode material additive.
[0027] The mixed ion conductor material provided by the present invention is x A y Zr 2-y Si x-y-1 P 4-x+y O 12 Solid electrolyte embedded in the carbon structure layer can provide a channel for the transmission of lithium ions and enhance the lithium ion conductivity of the material; at the same time, coating the outer layer of the material with a carbon layer can reduce the interface resistance between the material and the positive and negative electrodes, and block the unstable reaction between the positive and negative electrodes, making it more compatible with the positive and negative electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0029] Figure 1 is a schematic structural diagram of a mixed ion conductor material provided by an embodiment of the present invention;
[0030] Figure 2 is a flow chart of a method for preparing a mixed ion conductor material provided by an embodiment of the present invention;
[0031] Figure 3 is a scanning electron microscope (SEM) image of the mixed ion conductor material provided in Example 1 of the present invention;
[0032] Figure 4 is a SEM image of the mixed ion conductor material provided in Example 2 of the present invention;
[0033] Figure 5 is a Raman spectrum of the mixed ion conductor material provided in Example 2 of the present invention;
[0034] Figure 6 is a SEM image of the mixed ion conductor material provided in Example 3 of the present invention;
[0035] Figure 7 is the electrochemical impedance spectroscopy (EIS) of the mixed ion conductor material provided in Example 3 of the present invention;
[0036] Figure 8 is a SEM image of the mixed ion conductor material provided in Example 4 of the present invention;
[0037] Fig. 9 This is the EIS spectrum of the mixed ion conductor material provided in Example 4 of the present invention. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0039] The embodiment of the present invention provides a mixed ion conductor material, including a core and a shell two-layer structure, such as Figure 1 As shown; the core comprises a first component and a second component;
[0040] The first component is a solid electrolyte material with a chemical formula of Na x A y Zr 2-y Si x-y-1 P 4-x+y O 12 , wherein A includes one or more of Al, Cr, Fe, Ga, Se, Y, In or La, and 2.5≤x≤3.5, 0<y≤1;
[0041] The second component is amorphous carbon and / or crystalline carbon formed by carbonizing a carbonization precursor material, and the carbonization precursor material includes: one or more combinations of glucose, sucrose, citric acid, epoxy resin, phenolic resin, and urea-formaldehyde resin.
[0042] The second component is uniformly embedded and distributed in the first component, and the particle size of the formed core is between 30nm-100μm.
[0043] The outer shell is a carbon layer, and the structure of the carbon layer includes one or more components of a continuous film, a discontinuous film or closely arranged carbon particles; the thickness of the carbon layer is between 1nm-2μm, and the coverage rate of the carbon layer on the surface of the inner core is 50%-100%.
[0044] The mass ratio of the first component, the second component and the carbon layer is 1:(0-0.6):(0.002-0.6);
[0045] The shape of the mixed ion conductor material is one or more of spherical, ellipsoidal, pebble-shaped, flake-shaped or irregular shapes, and the particle size of the mixed ion conductor material particles is between 31nm-102μm.
[0046] The present invention provides a method for preparing the mixed ion conductor material. The specific steps are as follows: Figure 2 As shown, including:
[0047] Step 110, uniformly mixing the first component and the second component according to the required mass fraction to obtain a precursor powder;
[0048] Step 120, placing the precursor powder in a reaction device, raising the temperature from room temperature to 700° C.-1200° C. in an inert atmosphere, and keeping the temperature for 1 hour-20 hours, wherein the inert gas includes one or more of nitrogen, helium, neon, and argon;
[0049] Step 130, crushing the carbonized material to obtain a core material;
[0050] Step 140 , carbon-coating the core material to obtain a mixed ion conductor material with a core-shell structure.
[0051] Among them, the carbon coating method is specifically a liquid phase method or a solid phase method;
[0052] The liquid phase method includes: dissolving and mixing the core material and the soluble carbon source material in a solvent, and then drying the dried sample, and carbonizing the dried sample at 700°C-1200°C for 1 hour-20 hours;
[0053] The solid phase method comprises: mixing the core material and the solid phase carbon source material uniformly, and then carbonizing them at 700°C-1200°C in an inert atmosphere for 1 hour-20 hours.
[0054] The soluble carbon source material includes one or more of glucose, sucrose, citric acid, and epoxy resin;
[0055] The solid carbon source material includes: one or more of graphite, activated carbon, carbohydrate, acetylene black, mesoporous carbon, graphene, phenolic resin, furfural resin, urea-formaldehyde resin, asphalt, polyvinyl chloride, polyethylene glycol, and polyvinyl butyral.
[0056] An embodiment of the present invention provides an application of the mixed ion conductor material of the first aspect. The mixed ion conductor material can be used as a battery positive electrode material additive, a diaphragm coating material additive, a diaphragm coating material or a negative electrode material additive.
[0057] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the mixed ion conductor material of the present invention are respectively described below with multiple specific examples.
[0058] Example 1
[0059] This embodiment provides a method for preparing a mixed ion conductor material, and the specific steps are as follows:
[0060] The first component solid electrolyte material Na 3.1 Al 0.1 Zr 1.9 Si2PO 12 The epoxy resin, which is a carbonized precursor material of the second component, is uniformly mixed in a mixer at a mass ratio of 1:0.06 to obtain a mixed powder material of the first component and the second component.
[0061] The mixed powder material was heated to 800° C. at 5° C. / min in a nitrogen atmosphere in an atmosphere furnace and kept at this temperature for 4 hours to fully carbonize the carbonization precursor material.
[0062] After the heat preservation is completed, the temperature is naturally lowered to room temperature, and the carbonized material is crushed to a particle size of 4 μm by coarse crushing and fine crushing to obtain a core material.
[0063] The above core material and sucrose are placed in a VC mixer at a mass ratio of 1:0.1, deionized water is added, the mixture is fully mixed and then dried. The dried mixture is heated to 850°C at 5°C / min in a nitrogen atmosphere furnace, kept warm for 5 hours, and cooled to room temperature to obtain a mixed ion conductor material with a core-shell structure.
[0064] The SEM image of the mixed ion conductor material prepared in this example is as follows: Figure 3 stated; from Figure 3 It can be seen that the material as a whole presents an irregular shape, and the surface is covered with a discontinuous flaky carbon layer.
[0065] Example 2
[0066] This embodiment provides a method for preparing a mixed ion conductor material, and the specific steps are as follows:
[0067] The solid electrolyte material Na with a particle size of 1 μm 3.1 Al 0.1 Zr 1.9 Si2PO 12 The first component and the second component carbonization precursor material phenolic resin with a particle size of 1 μm are evenly mixed in a three-dimensional mixer at a mass ratio of 1:0.08 to obtain a mixed powder material of the first component and the second component.
[0068] The mixed powder material was transferred to a tubular furnace, and nitrogen was introduced at a flow rate of 0.5 L / min to exclude air. The temperature was raised to 820° C. at a rate of 5° C. / min and kept at this temperature for 6 hours to fully carbonize the carbonization precursor material.
[0069] After the heat preservation is completed, the temperature is naturally lowered to room temperature, and the carbonized material is crushed to a particle size of 4 μm by coarse crushing and fine crushing to obtain a core material.
[0070] The core material and asphalt powder were fully mixed in a high-speed mixer at a mass ratio of 1:0.1. The mixed material was heated to 900°C at 8°C / min in a nitrogen atmosphere furnace and kept warm for 5 hours before being cooled to room temperature to obtain a mixed ion conductor material with a core-shell structure.
[0071] The SEM image of the mixed ion conductor material prepared in this example is as follows: Figure 4 As shown;
[0072] The Raman spectrum of the mixed ion conductor material prepared in this embodiment is as follows: Figure 5 As shown, from Figure 5 In the Raman spectrum of the material, it can be obtained that the intensity ratio of the D peak to the G peak is 0.82, indicating that the surface carbon layer of the mixed ion conductor material prepared in this embodiment is mainly composed of an amorphous carbon layer.
[0073] Example 3
[0074] This embodiment provides a method for preparing a mixed ion conductor material, and the specific steps are as follows:
[0075] The solid electrolyte material Na with a particle size of 1 μm 2.97 Cr 0.07 Zr 1.93 Si 1.9 P 1.1 O 12 Glucose powder, which is a carbonized precursor material of the second component and has a particle size of 0.8 μm, is fully ground and mixed evenly in a mortar in a mass ratio of 1:0.12 to obtain a mixed powder material of the first component and the second component.
[0076] The mixed powder material was transferred to a tubular furnace and nitrogen was introduced to protect the furnace, the air was excluded, the temperature was increased to 800°C at a rate of 5°C / min, and the temperature was kept for 2 hours to fully carbonize the carbonization precursor material.
[0077] After the heat preservation is completed, the temperature is naturally lowered to room temperature, and the carbonized material is crushed to a particle size of 4 μm by coarse crushing and fine crushing to obtain a core material.
[0078] The core material and polyethylene glycol powder were fully mixed in a ball mill at a mass ratio of 1:0.1. The mixed material was heated to 800°C at 3°C / min in a nitrogen atmosphere furnace and kept warm for 3 hours. After the insulation, the temperature was lowered to room temperature to obtain a mixed ion conductor material with a core-shell structure.
[0079] The SEM image of the mixed ion conductor material prepared in this example is as follows: Figure 6 As shown;
[0080] The EIS spectrum of the mixed ion conductor material prepared in this example is as follows: Figure 7 As shown; from the EIS spectrum, it can be concluded that the resistance of the mixed ion conductor material after carbon coating is relatively small, and the ionic conductivity is improved to a certain extent.
[0081] Example 4
[0082] This embodiment provides a method for preparing a mixed ion conductor material, and the specific steps are as follows:
[0083] The first component solid electrolyte material Na 3.2 Cr 0.25 Zr 1.75 Si 1.95 P 1.05 O 12 The first component and the second component carbonization precursor material citric acid are ground and mixed in a mortar at a mass ratio of 1:0.2 to obtain a mixed powder material of the first component and the second component.
[0084] The mixed powder material was placed in a tubular furnace, nitrogen was introduced, the temperature was raised to 720° C. at a rate of 6° C. / min, and the temperature was kept for 6 hours to fully carbonize the carbonization precursor material.
[0085] After the heat preservation is completed, the temperature is naturally lowered to room temperature, and the carbonized material is ground and sieved to obtain the core material.
[0086] The core material and phenolic resin powder were fully mixed in a ball mill at a mass ratio of 1:0.2. The mixed material was heated to 900°C at 6°C / min in a nitrogen atmosphere furnace and kept warm for 4 hours. After the insulation, the temperature was lowered to room temperature to obtain a mixed ion conductor material with a core-shell structure.
[0087] The SEM image of the mixed ion conductor material prepared in this example is as follows: Figure 8 As shown;
[0088] The EIS spectrum of the mixed ion conductor material prepared in this example is as follows: Fig. 9 shown.
[0089] Example 5
[0090] This embodiment provides a method for preparing a mixed ion conductor material, and the specific steps are as follows:
[0091] The first component solid electrolyte material Na 2.97 Al 0.07 Zr 1.93 Si 1.9 P 1.1 O 12 The epoxy resin, which is a carbonized precursor material of the second component, is fully mixed in a double-motion mixer at a mass ratio of 1:0.15 for 1 hour to obtain a mixed powder material of the first component and the second component.
[0092] Then, the core material is prepared according to the carbonization process of Example 1.
[0093] The obtained core material is then mixed with sucrose according to the carbon coating process of Example 1 to prepare a mixed ion conductor solid electrolyte material.
[0094] Example 6
[0095] This embodiment provides a method for preparing a mixed ion conductor material, and the specific steps are as follows:
[0096] The first component solid electrolyte material Na3Ga 0.15 Zr 1.85 Si 1.85 P 1.15 O 12 The material and the second component carbonization precursor material sucrose are fully mixed in a double-motion mixer at a mass ratio of 1:0.08 for 1 hour to obtain a mixed powder material of the first component and the second component.
[0097] The mixed powder material was heated to 850° C. at 5° C. / min in an atmosphere furnace under a nitrogen environment and kept at this temperature for 5 hours to fully carbonize the carbonization precursor material.
[0098] After the heat preservation is completed, the temperature is naturally lowered to room temperature, and the carbonized material is crushed to micron level by coarse crushing and fine crushing to obtain the core material.
[0099] The core material and asphalt are uniformly mixed in a double-motion mixer at a mass ratio of 1:0.1, and then the mixed material is subjected to the carbon coating process of Example 2 to prepare a mixed ion conductor solid electrolyte material.
[0100] Example 7
[0101] This embodiment provides a method for preparing a mixed ion conductor material, and the specific steps are as follows:
[0102] The first component solid electrolyte material Na 2.8 Al 0.2 Fe 0.1 Zr 1.7 Si 1.5 P 1.5 O 12 The first component and the second component carbonization precursor material glucose are fully ground and mixed at a mass ratio of 1:0.12 to obtain a mixed powder material of the first component and the second component.
[0103] Then, the core material is prepared according to the carbonization process of Example 3.
[0104] The obtained core material is then coated with polyethylene glycol according to the coating operation of Example 3 to obtain a mixed ion conductor solid electrolyte material.
[0105] Example 8
[0106] This embodiment provides a method for preparing a mixed ion conductor material, and the specific steps are as follows:
[0107] The first component solid electrolyte material Na 3.2 Fe 0.1 Cr 0.15 Zr 1.75 Si 1.95 P 1.05 O 12 The first component and the second component carbonization precursor material epoxy resin are fully ground and mixed at a mass ratio of 1:0.15 to obtain a mixed powder material of the first component and the second component.
[0108] Then, the core material is prepared according to the carbonization process of Example 1.
[0109] The obtained core material is then coated with polyethylene glycol according to the coating operation of Example 3 to obtain a mixed ion conductor solid electrolyte material.
[0110] The mixed ion conductor material provided by the invention can be used as a positive electrode material additive, a diaphragm coating material additive, a diaphragm coating material, and a negative electrode material additive for batteries; it has the advantages of good compatibility with positive and negative electrodes and low interface resistance.
[0111] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A mixed ion conductor material, characterized in that: The mixed ion conductor material is a core-shell structure, including a core and an outer shell; The inner core comprises a first component and a second component; The first component is a solid electrolyte material with a chemical formula of Na x A y Zr 2-y Si x-y-1 P 4-x+y O 12 , wherein A includes one or more of Al, Cr, Fe, Ga, Se, Y, In or La, and 2.5≤x≤3.5, 0<y≤1; The second component is amorphous carbon and / or crystalline carbon formed by carbonization of a carbonization precursor material; The shell is a carbon layer; The carbonization precursor material includes: one or more combinations of glucose, sucrose, citric acid, epoxy resin, phenolic resin, and urea-formaldehyde resin; The mass ratio of the first component, the second component and the carbon layer is 1:(0-0.6):(0.002-0.6).
2. The mixed ion conductor material according to claim 1, characterized in that The structure of the carbon layer is specifically composed of one or more of a continuous film, a discontinuous film or closely arranged carbon particles; the thickness of the carbon layer is between 1nm-2μm, and the coverage of the carbon layer on the surface of the core is 50%-100%; The second component is uniformly embedded and distributed in the first component, and the particle size of the formed core is between 30nm-100μm; The particle size of the mixed ion conductor material is between 31 nm and 102 μm.
3. The mixed ion conductor material according to claim 1, characterized in that The shape of the mixed ion conductor material is one or more of spherical, ellipsoidal, pebble-shaped, flake-shaped or irregular.
4. A method for preparing the mixed ion conductor material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Uniformly mixing the first component and the second component according to the required mass fraction to obtain a precursor powder; The precursor powder is placed in a reaction device and heated from room temperature to 700°C under an inert atmosphere. -1200℃, keep warm for 1 hour to 20 hours; crushing the carbonized material to obtain a core material; The core material is carbon coated to obtain a mixed ion conductor material with a core-shell structure.
5. The method for preparing a mixed ion conductor material according to claim 4, characterized in that: The inert atmosphere includes one or more of nitrogen, helium, neon and argon.
6. The method for preparing a mixed ion conductor material according to claim 4, characterized in that: The carbon coating method is specifically a liquid phase method or a solid phase method; The liquid phase method comprises: dissolving and mixing the core material and the soluble carbon source material in a solvent, and then drying the dried sample, and carbonizing the dried sample at 700° C.-1200° C. for 1 hour-20 hours; The solid phase method comprises: mixing the core material and the solid phase carbon source material uniformly, and then carbonizing them at 700° C. to 1200° C. in an inert atmosphere for 1 hour to 20 hours.
7. The method for preparing a mixed ion conductor material according to claim 6, characterized in that: The soluble carbon source material includes: one or more of glucose, sucrose, citric acid, and epoxy resin; The solid carbon source material includes one or more of graphite, activated carbon, carbohydrate, acetylene black, mesoporous carbon, graphene, phenolic resin, furfural resin, urea-formaldehyde resin, asphalt, polyvinyl chloride, polyethylene glycol, and polyvinyl butyral.
8. An application of the mixed ion conductor material according to any one of claims 1 to 3, characterized in that: The mixed ion conductor material can be used as a positive electrode material additive, a separator coating material additive, a separator coating material or a negative electrode material additive for a battery.
Citation Information
Patent Citations
In-situ composite lithium battery negative electrode material and preparation method and application thereof
CN110034280A
Carbon-coated solid electrolyte material as well as preparation method and application thereof
CN111403806A